Socially creative activities in Psychologically Informed Planned Environments: engaging and relating in the Offender Personality Disorder Pathway. Issue 3 (13th August 2018) - Ryan, Sue; Benefield, Nick; Baker, Vikki
Abstract : Purpose: Major developments in the management of and intervention for people with significant personality difficulties who have offended are continuing, most recently with the implementation of the Offender Personality Disorder (Department of Health/National Offender Management Service (DoH/NOMS), 2011 ) Pathway. Included in this, is the Psychologically Informed Planned Environment model, currently being implemented in Prisons and Probation Approved Premises. This model includes the provision of "socially creative activities" (Benefield et al., 2018 ), opportunities for social learning and relationship building. The purpose of this paper is to explore the rationale for and examples of the implementation of these. Design/methodology/approach: The paper offers a narrative review of research around child development, personality, social learning and the policy context around the OPD Pathway. An overview of the socially creative sessions and a rationale for them is provided. Findings: A conceptual understanding of the rationale for socially creative sessions is provided with a description of the sessions that focussed upon development of imagination, narrative/story making, social expression and relational experiences, i.e. singing, drama and reading with others. It is argued that the activities offered opportunities to engage in a different medium for expression, learning and relating, that may provide a catalyst for change in individuals with entrenched motivational and interpersonal difficulties. Research limitations/implications: This is a conceptual paper that provides a rationale for socially creative sessions and describes the sessions. This paper does not feature outcome data which are outside the remit of this paper; however, future research into the impact of this approach to aid relational development and assist in emotional and behavioural stability is essential. Practical implications: The complex needs of this client group emphasise the need for services to offer holistic ways to engage people who can have a positive impact upon relationships. Originality/value: The work presented in this paper is valuable for professionals working within the personality disorder and criminal justice field, also for policy makers and commissioners.